Mencari Kebebasan Dalam Tasawuf: Telaah Kritis Konsep Mahabbah - Asep Ahmad Arsyul (Ma'had Aly Idrisiyyah, 2024)
In Sufi practice, mahabbah (divine love) is the essence of the spiritual relationship between humans and God. This paper critically examines how the concept of mahabbah relates to the idea of human freedom. Through a comprehensive analysis of classical and contemporary references, this research explores the contradictions that arise between mahabbah and human freedom. The study reveals that in the Sufi tradition, mahabbah is viewed as a noble spiritual state. Love has the ability to enhance one's journey towards Allah, soften hardened hearts, and lead individuals to obedience to Him. Allah is perceived as a Being of absolute perfection and beauty, so the results of this love are positive and contribute to the inner beauty and perfection of actions and behavior of the seeker. However, a critical question quickly arises: Does this surrender in divine love hinder individual freedom or is it actually a means to achieve true freedom? This paper aims to: (1) Identify the monotheistic aspects of mahabbah found in Islamic mysticism, (2) review the dialectical interaction between mahabbah and human freedom, and (3) provide a new perspective in gaining an understanding of spiritual freedom through the Sufi approach. The research reveals that in Sufism, achieving true freedom is actually found through devotion to divine love. This study is an important part of the broader discussion on the role of humans in Islamic spirituality, emphasizing the complex relationship between divine love, freedom, and the pinnacle of spiritual achievement in Sufism. Keywords: Mahabbah, Freedom, Sufism